Predictive factors for recurrent febrile seizures in children - Pengekuten Marudur; Elisabeth Herini; Cahya Dewi Satria (Indonesian Pediatric Society, 2012)
Background Oneô€¡third of children who experience febrile seizureshave a recurrence, 'V̇ith rates of75% in the first year, and 90% mthinthe second year following the first febrile seizure. Predictive factorsfor recurrent febrile seizures have been reported in studies from othercountries, but there have been few of these studies in Indonesia.Objective To determine predictive factors for the recurrence offebrile seizures in children.Methods Children w i t h firstô€¡time febrile seizures wereprospectively followed up, for at least 12 months. Subjects wererecruited consecutively from August 2008 to April 20 1 0 from twohospitals in Yogyakarta and one hospital in Klaten. We monitoredrecurrences of febrile seizure by telephone or home visits to parentsevery 3 months. Time to first recurrence of febrile seizures wasanalyzed using the Cox regression model.Results T here were 196 children v,ith firstô€¡time febrile seizures whocompleted the follow up. Recurrent seizures were observed in 56children (28.6%). Me811 follow up time was 21.7 (SD 6.6) months.Temperature of <40